Description of three new species of predatory Genus Hexacentrus (Orthoptera: Tettigoniidae) from India, with bioacoustic and morphological characterizations - Ghosh, Aarini; Jaiswara, Ranjana; Monaal; Sabharwal, Shagun; Dasoju, Vivek; Bhattacharjee, Anubhab; Rajaraman, Bittu Kaveri (Zootaxa, 2023)
Hexacentrus is a genus of predatory katydids. In India, the genus Hexacentrus is represented by 7 species of which 6 are morphologically characterized while one is only acoustically characterized. In this study, we describe three new species under the genus from India based on detailed morphological, stridulatory, and acoustic features.